1976
DOI: 10.1152/ajplegacy.1976.231.5.1533
|View full text |Cite
|
Sign up to set email alerts
|

Regulation of plasma calcium in rats: age-related roles of PTH and calcitonin

Abstract: To determine the influence of aging on the relative roles of parathyroid hormone (PTH) and calcitonin in the control of calcium homeostasis during fasting, we assessed changes in plasma calcium in fasted rats following simultaneous removal of the glands that secrete both hormones. Animals ranging in age from 3 to 34.7 wk were thyroparathyroidectomized or sham operated and bled by orbital puncture prior to and 1.5, 3, and 6 h after surgery. After thyroparathyroidectomy (TPTX), plasma calcium fell immediately an… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
12
0

Year Published

1982
1982
2020
2020

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 11 publications
(12 citation statements)
references
References 0 publications
0
12
0
Order By: Relevance
“…The serum calcium concen trations of the starved rats are significantly lower than those of the controls, and the starved rats lose approxi mately 25-30% of their initial body weight [Shires et al, 1980]. In addition, it has been demonstrated that in the fasting state the relative importance of calcitonin and parathyroid hormone in regulation of serum calcium varies with age, and parathyroid hormone plays a do minant role in young rats [Kalu and Foster, 1976]. We have pointed out that the serum calcium concentrations of the starved mice are not changed and the body weights of the test animals show a significant decrease as compared to those of the control animals.…”
Section: Discussionmentioning
confidence: 99%
“…The serum calcium concen trations of the starved rats are significantly lower than those of the controls, and the starved rats lose approxi mately 25-30% of their initial body weight [Shires et al, 1980]. In addition, it has been demonstrated that in the fasting state the relative importance of calcitonin and parathyroid hormone in regulation of serum calcium varies with age, and parathyroid hormone plays a do minant role in young rats [Kalu and Foster, 1976]. We have pointed out that the serum calcium concentrations of the starved mice are not changed and the body weights of the test animals show a significant decrease as compared to those of the control animals.…”
Section: Discussionmentioning
confidence: 99%
“…It is widely accepted that calcitonin increases intracellular calcium (Ca 2+ ) levels and calcium acts as an important secondary messenger and plays a role in a series of cellular functions such as cell proliferation, cell differentiation, and fetal development (Li, Shen, Chang, Hsu, & Sung, 2008). Also, it has been reported that increased intracellular calcium concentration can lead to increased blastocyst formation and implantation (Kalu & Foster, 1976). It was found that after fertilization, the uterine endometrium begins to express calcitonin, and the calcitonin expression reaches the highest level during the implantation window (Ding, Zhu, Bagchi, & Bagchi, 1994;Kumar et al, 1998;Zhu, Cullinan-Bove, Polihronis, Bagchi, & Bagchi, 1998).…”
Section: Injection Of Calcitonin Before Uterine Implantation Windowmentioning
confidence: 99%
“…It has become apparent as a result of physiological studies that starvation had an effect on calcium metabolism (Kalu and Foster, 1976 Asch and Asch, 1981). Recent morphological reports have suggested that in the chief cells of the parathyroid glands in the starved mice (Isono et al, 1985) and golden hamsters ) the number of lipid droplets were increased as compared to those of the control animals.…”
Section: Discussionmentioning
confidence: 99%
“…Physiological studies have shown that starvation had an effect on calcium metabolism (Kalu and Foster, 1976;Asch, 1978;Beck et al, 1979;Pak and Galosy, 1979;Shires et al, 1980;Asch and Asch, 1981). Recent morphological reports have suggested the changes of the parathyroid glands in starved mice (Isono et al , 1985) and starved golden hamsters .…”
Section: Starvationmentioning
confidence: 99%